2018
DOI: 10.5152/ejbh.2018.3712
|View full text |Cite
|
Sign up to set email alerts
|

Sentinel Lymph Node Metastasis in Invasive Lobular Carcinoma of the Breast

Abstract: Objective: Invasive lobular carcinoma (ILC) of the breast makes up 5 to 15 percent of all invasive breast cancers. It has distinctive clinical and histopathological features when compared to invasive ductal carcinoma (IDC). This study intends to describe factors influencing sentinel lymph node (SLN) positivity in patients with "pure" ILC. Materials and Methods:Data of 105 patients, who were treated at a tertiary oncology center, with lobular carcinoma of the breast that were subjected to SLN biopsy was probed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 13 publications
1
3
0
Order By: Relevance
“…The predictors for the involvement of lymph nodes have been widely studied, while the risk factors for positive SLNs have rarely been explored. We found that tumor size was the only influencing factor affecting positive rate of SLNs in participants with ILC, which was in line with a previous study (23). For patients with IDC, age at diagnosis, molecular subtype, and pathologic tumor size were independent factors for the positive rate of SLNs.…”
Section: Discussionsupporting
confidence: 91%
“…The predictors for the involvement of lymph nodes have been widely studied, while the risk factors for positive SLNs have rarely been explored. We found that tumor size was the only influencing factor affecting positive rate of SLNs in participants with ILC, which was in line with a previous study (23). For patients with IDC, age at diagnosis, molecular subtype, and pathologic tumor size were independent factors for the positive rate of SLNs.…”
Section: Discussionsupporting
confidence: 91%
“…Sentinel lymph node biopsy in clinically axillary node negative patients Following the first successful report of SLNB (14,15), this technique was rapidly introduced to clinical practice in cT1-2 patients with clinically axillary node negative (16)(17)(18)(19)(20)(21). Overall identification rate of SLNB and the false negative rate (FNR) of SLNB are over 90% and under 10%, respectively (Table 1) (22)(23)(24)(25)(26)(27)(28)(29)(30).…”
Section: Clinical and Research Consequencesmentioning
confidence: 99%
“…1 Previous retrospective analyses have demonstrated that ILC is more likely to present with extensive disease that is underappreciated on preoperative imaging. 2 , 3 Given that the size of ILC has been associated with an increased risk of sentinel lymph node metastasis, 4 , 5 this underestimation in ILC size from imaging calls into question whether avoidance of routine SLNBx in patients with ILC over 70 years of age is oncologically safe and appropriate.…”
mentioning
confidence: 99%